Design and Motion Analysis of Polishing Robot with 3-RSS Coaxial Drive Layout Parallel Mechanism - Hongxiang Jing; Huibin Qin; Zhili Hou; Linlin Liu; Junqi Liu; Zongyan Wang (Jixie chuandong)
In view of the present series polishing robot has the problem of insufficient stiffness when grinding spherical， a 3-RSS coaxial drive layout type parallel mechanism tool grinding robot is put forward. The coaxial drive layout is a way of arranging the drives on the same axis. The robot composed of a central base column and three actuated rotating arm that can rotate around this column， each arm is connected by distal linkages to an end polisher. A coaxial driving layout polishing robot model is established through configuration analysis and structural design， and then performs kinematic analysis on the model， the singular position is analyzed through the Jacobian matrix， and a flexible working space for the polisher is obtained. Comparing the preset paths through motion simulation， the motion error analysis with the simulation trajectory verifies the feasibility of the driving scheme. It provides theoretical and technical support for the parallel mechanism grinding robot to expand the working space and improve the stiffness.